1991
DOI: 10.1128/mcb.11.9.4545
|View full text |Cite
|
Sign up to set email alerts
|

The serum response factor is extensively modified by phosphorylation following its synthesis in serum-stimulated fibroblasts.

Abstract: Growth factor regulation of c-fos proto-oncogene transcription is mediated by a 20-bp region of dyad symmetry, termed the serum response element. The inner core of this element binds a 67-kDa phosphoprotein, the serum response factor (SRF), that is thought to play a pivotal role in the c-fos transcriptional response. To investigate the mechanism by which SRF regulates c-fos expression, we generated polyclonal anti-SRF antibodies and used these antibodies to analyze the biochemical properties of SRF. These stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 55 publications
5
46
0
1
Order By: Relevance
“…Maximal message accumulation (eightfold) occurs between 60 ± 120 min after stimulation, and begins to decline by 180 min after stimulation. The time course of SRF message accumulation mimics that of SRF message accumulation seen after serum-starved ®broblasts are stimulated with 20% fetal bovine serum (Misra et al, 1991), or bFGF (Spencer et al, 1999).…”
Section: Lpa Induces Expression Of the Endogenous Srf Genementioning
confidence: 64%
See 4 more Smart Citations
“…Maximal message accumulation (eightfold) occurs between 60 ± 120 min after stimulation, and begins to decline by 180 min after stimulation. The time course of SRF message accumulation mimics that of SRF message accumulation seen after serum-starved ®broblasts are stimulated with 20% fetal bovine serum (Misra et al, 1991), or bFGF (Spencer et al, 1999).…”
Section: Lpa Induces Expression Of the Endogenous Srf Genementioning
confidence: 64%
“…Previously, we (Misra et al, 1991;Spencer and Misra, 1996) and others (Norman et al, 1988) have demonstrated that in response to serum stimulation the SRF gene is rapidly induced at the transcriptional level in a protein synthesis independent manner. In murine ®broblasts SRF gene expression is transient.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations